The Importance of Vacuolar Ion Homeostasis and Trafficking in Hyphal Development and Virulence in Candida albicans - Lv, Quanzhen; Yan, Lan; Jiang, Yuanying (Frontiers in Microbiology, 2021)
The vacuole of Candida albicans plays a significant role in many processes including homeostasis control, cellular trafficking, dimorphic switching, and stress tolerance. Thus, understanding the factors affecting vacuole function is important for the identification of new drug targets needed in response to increasing levels of invasive infections and the growing issue of drug resistance in the world. Past studies have shown that vacuolar proton-translocating ATPases (V-ATPases) play a central role in pH homeostasis and filamentation. Vacuolar protein sorting components (VPS) regulate V-ATPases assembly and at the same time affect hyphal development. As well, vacuolar calcium exchange systems like Yvc1 and Pmc1 maintain cytosolic calcium levels while being affected by V-ATPases function. All these proteins play a role in the virulence and pathogenesis of C. albicans. This review highlights the relationships among V-ATPases, VPS, and vacuolar calcium exchange proteins while summarizing their importance in C. albicans infections.